Effects of the Oral Administration of Aqueous and Methanolic Leaf Extracts of Chenopodium ambrosioides L. (Amaranthaceae) on Blood Glucose Levels in Wistar Rats - Kasali, Félicien Mushagalusa; Kadima, Justin Ntokamunda; Tusiimire, Jonans; Ajayi, Clement Olusoji; Agaba, Amon Ganafa (Journal of Experimental Pharmacology, 2022)
Background: Diabetes mellitus is a metabolic disorder that poses a major global health threat. The current diabetes mellitus uses insulin and oral hypoglycemic agents, which have limitations, including adverse effects and secondary failures. Herbal medicine is being evaluated for its role in the pharmacotherapy of diabetes. This study was aimed to assess the anti-diabetic potential and shortterm toxicity level of Chenopodium ambrosioides collected from Bukavu in Democratic Republic of Congo. Methods: Leaves of C. ambrosioides were extracted by infusion and maceration with distilled water and 95% methanol, respectively. Hypoglycemic and antihyperglycemic potentials of the aqueous and methanolic were investigated in normoglycemic and intraperitoneal glucose-loaded rats at 100, 200, and 400 mg/kg body weight. An oral acute toxicity test was carried out on healthy female Wistar rats. Results: Acute toxicity test showed the mean lethal dose (LD50) for both aqueous and methanol extracts of C. ambrosioides to be more than 2000 mg/kg. The group treated with glibenclamide (5 mg/kg b.w) and aqueous extract of the plant (200 mg/kg b.w) showed a significant reduction (p< 0.0001 and p< 0.05) of fasting blood glucose by 46.91% and 16.72%, respectively, compared to control and all other treatment groups. In acute conditions, a single oral administration of the aqueous and methanolic extracts lowered fasting blood glucose in rats. Any manifestation and signs of toxicity and mortality have been recorded for 14 days of observation. Conclusion: Leaf aqueous and methanolic extracts of C. ambrosioides appeared safe at 2000 mg/kg. The plant demonstrated some anti-diabetic potential in rats, explaining its use as an anti-diabetic remedy locally.
Keywords: Chenopodium ambrosioides; Anti-diabetic activity; Fasting blood glucose; IGTT; LD50